Analysis of plasmaspheric hiss wave amplitudes inferred from low‐altitude POES electron data: Validation with conjunctive Van Allen Probes observations. Issue 10 (26th October 2015) - de Soria‐Santacruz, M.; Li, W.; Thorne, R. M.; Ma, Q.; Bortnik, J.; Ni, B.; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.
Abstract: Plasmaspheric hiss plays an important role in controlling the overall structure and dynamics of the Earth's radiation belts. The interaction of plasmaspheric hiss with radiation belt electrons is commonly evaluated using diffusion codes, which rely on statistical models of wave observations that may not accurately reproduce the instantaneous global wave distribution or the limited in situ satellite wave measurements. This paper evaluates the performance and limitations of a novel technique capable of inferring wave amplitudes from low‐altitude electron flux observations from the Polar Orbiting Environmental Satellites (POES), which provide extensive coverage in shell and magnetic local time (MLT). We found that, within its limitations, this technique could potentially be used to build a dynamic global model of the plasmaspheric hiss wave intensity. The technique is validated by analyzing the conjunctions between the POES spacecraft and the Van Allen Probes from September 2012 to June 2014. The technique performs well for moderate‐to‐strong hiss activity (≥30 pT) with sufficiently high electron fluxes. The main source of these limitations is the number of counts of energetic electrons measured by the POES spacecraft capable of resonating with hiss waves. For moderate‐to‐strong hiss events, the results show that the wave amplitudes from the EMFISIS instruments on board the Van Allen Probes are well reproduced by the POES technique, which provides more consistent estimates than the parameterized statistical hiss wave model based on CRRES data. Key Points: Determined the performance and limitations of the POES technique applied to hiss waves The POES technique performs well for moderate‐to‐strong hiss events at L>4 97% of the inferred amplitudes are within a factor of 2.5 of the EMFISIS measurements